Translating Dental, Oral, and Craniofacial Regenerative Medicine Innovations to the Clinic through Interdisciplinary Commercial Translation Architecture. (September 2021) - Taylor, D.P.; Yoshida, M.; Fuller, K.; Giannobile, W.V.; Sfeir, C.S.; Wagner, W.R.; Kohn, D.H.
Few university-based regenerative medicine innovations in the dental, oral, and craniofacial (DOC) space have been commercialized and affected clinical practice in the United States. An analysis of the commercial translation literature and National Institute for Dental and Craniofacial Research's (NIDCR's) portfolio identified barriers to commercial translation of university-based DOC innovations. To overcome these barriers, the NIDCR established the Dental Oral Craniofacial Tissue Regeneration Consortium. We provide generalized strategies to inform readers how to bridge the "valley of death" and more effectively translate DOC technologies from the research laboratory or early stage company environment to clinical trials and bring needed innovations to the clinic. Three valleys of death are covered: 1) from basic science to translational development, 2) from translational technology validation to new company formation (or licensing to an existing company), and 3) from new company formation to scaling toward commercialization. An adapted phase-gate model is presented to inform DOC regenerative medicine teams how to involve regulatory, manufacturability, intellectual property, competitive assessments, business models, and commercially oriented funding mechanisms earlier in the translational development process. An Industrial Partners Program describes how to conduct market assessments, industry maps, business development processes, and industry relationship management methods to sustain commercial translation through the later-stage valley of death. Paramount to successfully implementing these methods is the coordination and collaboration of interdisciplinary teams around specific commercial translation goals and objectives. We also provide several case studies for translational projects with an emphasis on how they addressed DOC biomaterials for tissue regeneration within a rigorous commercial translation development environment. These generalized strategies and methods support innovations within a university-based and early stage company-based translational development process, traversing the many funding gaps in dental, oral, and craniofacial regenerative medicine innovations. Although the focus is on shepherding technologies through the US Food and Drug Administration, the approaches are applicable worldwide.